ANALISIS BUDAYA BARU PENGGUNAAN MASKER DALAM BERKOMUNIKASI (STUDI KASUS PENGGUNAAN MASKER SAAT WABAH COVID 19 DALAM BERKOMUNIKASI PADA MASYARAKAT) - Trisnawati Kusumawardhani (Interpretasi: Communication & Public Relations, 2021)
The Covid 19 outbreak has had a huge impact on human life. Both midwives for education, economy, and entertainment. There is a necessity in carrying out health protocols, namely to always use a mask when on the move outside the home, always carry out physical distancing, and wash your hands as often as possible. This led to the emergence of a new culture in society. A new culture that changes the level of human life, and ethical and aesthetic values. Before this pandemic hit, people who wore masks when talking to others were considered impolite and less respectful of their interlocutors. The process of interpersonal communication becomes a little disturbed by not being able to see the non-verbal response of the communicant, namely facial expressions and smiles. People who have to wear masks often feel discomfort while doing activities outside the home. Some medical professionals recommend changing the mask after being used for 3- 4 hours continuously during work activities. Now the use of masks has become a new culture not only in one country but a new culture in all countries.